_WELCOMETO Radioland

Top50  











.




.








.














> > -

-

: 1/4

-

- - - - - - - - - - - - - - - - - - - 3

ࠠ - - - - - - - - - - - - - - - - - - - - - - 5

䠠 - - - - - - - - - - - - - - - - - - - - - - 8

 

- - - - - - - - - - - - - - - - - - - - - - 10

頠 - - - - - - - - - - - - - - - - - - - - - - 13

젠 - - - - - - - - - - - - - - - - - - - - - - 16

 

Š - - - - - - - - - - - - - - - - - - -

- - - - - - - - - - - - - - - - - - -

 

-

 

 

 

 

j(x,y) - , . (DEF) :

 

d2j + d2j = 0

dx2 dy2

( ABGH) - :

d2j + d2j = 0

dx2 dy2

q - e;

enn - ;

Nd(x,y) - ;

Na(x,y) - ;

e0 -

 

:

 

j| BC = Uu

j| DE = U

j| FG = Uc

j| AH = Un

 

AB GH:

 

dj = 0 dj = 0

dy AB dy GH

 

OY

:

 

dj = 0 dj = 0

dy DC dy EF

 

-

:

 

j| -0 = j| +0

eok Ex |-0 - enn Ex |+0 = - Qss

 

Qss - ;

eok - ;

enn - .

+0 -0 CF . - .

 

 

 

 

 

 

 

 

  {(x,y) : 0 < x < Lx , 0 < y < Ly }

 

W={(x,y) : 0 < i < M1 , 0 < j < M2}

x0 =0 , y0=0, xM1 = Lx , yM2 = Ly

xi+1 = xi + hi+1 , yj+1 = yj+ rj+1

i = 0,...,M1-1 j = 0,...,M2-1

 

 

 

 

 

:

xi+ ½ = xi + hi+1 , i = 0,1,...,M1-1

2

yj+ ½ = yj + rj+1 , j = 0,1,...,M2-1

2

:

U(xi,yj) = Uij

I(xi+½,yj) = Ii+½,j

I(xi,yj+½) = Ii,j+½

 

:

 

Dj = - q (Nd + Na)

e0en

 

Q(x,y)

:

Vij = { (x,y) : xi- ½ < x < xi+ ½ , yj- ½ < y < yj+ ½ }

 

xi+ ½ yj+ ½ xi+ ½ yj+ ½

ò ò Dj dxdy = ò ò Q(x,y)dxdy

xi- ½ yj- ½ xi- ½ yj- ½

:

yj+½ xi+½

ò(Ex(xi+½,y) - Ex(xi-½,y) )dx + ò(Ey(x,yj+½) - Ey(x,yj-½))dy=

yj-½ xi-½

 

xi+ ½ yj+ ½

= ò ò Q(x,y)dxdy

xi-   ½ yj- ½

:

Ex(x,y) = - dj(x,y)

dx (*)

Ey(x,y) = - dj(x,y)

dy

 

x - .

 

yj-½ < y < yj- ½ Ex(xi + ½,yj) = Ei+ ½ ,j = const

yj-½ < y < yj- ½ Ex(xi - ½ ,yj) = Ei- ½ ,j = const (**)

xi-½ < x < xi+ ½ Ey(xi, yj + ½) = Ei,j+ ½ = const

xi-½ < x < xi+ ½ Ey(xi, yj -½ ) = Ei,j - ½ = const

xi- ½ < x < xi+ ½

yj- ½ < y < yj+ ½ - Q(x,y) = Qij = const

 

 

(Ex)i+ ½ ,j - (Ex)i -½ ,j r*j + (Ey)ij+ ½ - (Ey)ij- ½ h*i = Qijh*i r*j

 

 

h*i = hi - hi+1 , r*j = rj - rj+1

2 2

i+ ½ ,j j(x,y) :

xi+1

òEx(x,yj)dx = - ji+1,j - jij

xi

(**) y=yj:

 

(Ex)i+ ½ ,j = - ji+1j - jij

hi+1

 

:

(Ey)i,j+ ½= - jij+1 - jij

rj+1

 

: